2018
DOI: 10.21815/jde.018.088
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Critical Thinking Skills Across a Dental Curriculum

Abstract: Critical thinking and problem-solving are two of the most frequently desired goals for dental student learning, but greater understanding is needed of how students' critical thinking skills develop from the beginning to the end of the curriculum. The aim of this study was to use students' performance on critical thinking assessments at five time points from the first to the fourth years to longitudinally assess their critical thinking development across the curriculum. In 2014-16, the performance of students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
0
11
1
1
Order By: Relevance
“…21 While the development of these skills can involve a variety of activities such as case analysis, simulation, and debates, the American Dental Education Association Commission on Change and Innovation (ADEA CCI) suggests that such activities be incorporated throughout dental curricula. 22 A longitudinal study by Everett et al 22 showed that University of Michigan dental students improve their critical thinking skills over the four year curriculum, however, the authors noted variability in assessments and influence of the culture of the academic environment as limitations to their study. Critical thinking requires higher-order cognitive skills, which can be assessed via higher-order cognition questions created using verbs on the upper "tiers" of Bloom's taxonomy and its revisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 While the development of these skills can involve a variety of activities such as case analysis, simulation, and debates, the American Dental Education Association Commission on Change and Innovation (ADEA CCI) suggests that such activities be incorporated throughout dental curricula. 22 A longitudinal study by Everett et al 22 showed that University of Michigan dental students improve their critical thinking skills over the four year curriculum, however, the authors noted variability in assessments and influence of the culture of the academic environment as limitations to their study. Critical thinking requires higher-order cognitive skills, which can be assessed via higher-order cognition questions created using verbs on the upper "tiers" of Bloom's taxonomy and its revisions.…”
Section: Introductionmentioning
confidence: 99%
“…Critical thinking, or the ability to give reasons for what one says or does, is viewed as a key component to education, and an essential skill for a health care provider to solve patient problems and deliver safe, efficient, and skillful care. 20,22 The Commission on Dental Accreditation (CODA) requires that predoctoral dental programs emphasize critical thinking and problem-solving in educating future dentists. 21 While the development of these skills can involve a variety of activities such as case analysis, simulation, and debates, the American Dental Education Association Commission on Change and Innovation (ADEA CCI) suggests that such activities be incorporated throughout dental curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Students are still included in the Beginning Thinker level on the critical thinking skills test. (Everett, Anderson, Wright & Fontana, 2018;Ramos, 2018). Chemistry is a difficult subject for students who seek interesting and applicative learning.…”
Section: Introductionmentioning
confidence: 99%
“…Once they have interpreted the validity and reliability of the information, dental professionals need to provide patients with reliable oral health information, practice evidence, and alternative treatment options. Therefore, dental education should encourage competence in critical thinking skills 5 …”
Section: Introductionmentioning
confidence: 99%